Enhancing Elementary School Students’ Cultural Awareness through the Siat Tipat Bantal Cultural Observation Activity - Monica Virly Egithareina Mahendra; Maria Goreti Rini Kristiantari; I Made Citra Wibawa (Mimbar Ilmu, 2025)
The lack of students’ direct experience with local cultural traditions and the limited availability of contextual learning media have resulted in low cultural awareness among elementary school students. This condition poses a risk of weakening the younger generation's concern for preserving local cultural heritage. This study aims to develop and examine the effectiveness of audiovisual learning media based on the Siat Tipat Bantal tradition to enhance the cultural awareness of elementary school students through the Profile of Pancasila Students approach. The type of research employed is Research and Development (R&D) using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The research subjects involved 19 fifth-grade students and several experts, including content experts, instructional design experts, media experts, teachers, and school principals. Data were collected using validation questionnaires, student response questionnaires, and achievement tests. The data were analyzed using descriptive quantitative, descriptive qualitative, and inferential statistical methods (t-test). The results revealed that the developed audiovisual media was of very high quality, with expert and practitioner validation scores exceeding 90%. Furthermore, the t-test results indicated a tvalue of 10.540, which is greater than the ttable value of 2.101, signifying a significant difference between students' pre-test and post-test scores. It can be concluded that the Siat Tipat Bantal audiovisual media is effective in enhancing the cultural awareness of elementary school students. Its implication suggests that this media can serve as an alternative contextual learning tool that promotes the strengthening of local cultural values in elementary education.